PENGARUH PENERAPAN MODEL PEMBELAJARAN PBL DENGAN PENDEKATAN TEACHING AT THE RIGHT LEVEL TERHADAP KEMAMPUAN REPRESENTASI MATEMATIS - Situmorang, Melany Maduma; Nurjamil, Dedi; Patmawati, Hetty (De Fermat : Jurnal Pendidikan Matematika, 2026)
This study aims to determine the effect of implementing the Problem-Based Learning model with the Teaching at the Right Level approach on students’ mathematical representation skills. This study uses a quantitative approach with a True Experimental Design using a Posttest-Only Control Design. The population of this study was all eighth-grade students at SMP Negeri 9 Tasikmalaya. The research sample was determined using simple random sampling, resulting in class VIII-F as the experimental class and VIII-E as the control class. The research instrument was a test, and the data obtained were analyzed using an independent samples t-test with the prerequisite tests of normality and homogeneity. The average test score in the experimental class was 7,55, which was higher than that of the control class, which was 6. The results of the independent samples t-test showed a sig. (2-tailed) value of 0.025, meaning that sig. (2-tailed) < 0.05, indicating that there was an effect of the application of the Problem-Based Learning model with the Teaching at the Right Level approach on students’ mathematical representation skills